2015
DOI: 10.1097/md.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Blood as a Substitute for Tumor Tissue in Detecting EGFR Mutations for Guiding EGFR TKIs Treatment of Nonsmall Cell Lung Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 47 publications
5
50
0
Order By: Relevance
“…Recent reports suggested that presence of mEGFR ctDNA is associated with longer PFS and OS in advanced NSCLC patients treated with EGFR‐TKIs . In this study, poor PFS and a trend toward shorter OS times were observed in lung adenocarcinoma patients with plasma mEGFR ctDNAs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Recent reports suggested that presence of mEGFR ctDNA is associated with longer PFS and OS in advanced NSCLC patients treated with EGFR‐TKIs . In this study, poor PFS and a trend toward shorter OS times were observed in lung adenocarcinoma patients with plasma mEGFR ctDNAs.…”
Section: Discussionsupporting
confidence: 52%
“…Recent reports suggested that presence of mEGFR ctDNA is associated with longer PFS and OS in advanced NSCLC patients treated with EGFR-TKIs. 23,24 In this study, poor PFS and a trend toward shorter OS times were observed in lung adenocarcinoma patients with plasma mEGFR ctDNAs. In addition, this analysis also showed that EGFR mutations in ctDNA were associated with shorter duration of disease control in advanced lung adenocarcinoma patients treated with EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 58%
“…Although no significant differences were observed in both ORR (P=0.489) and DCR (P=0.548) between the T+P+ and T+P-groups, the T+P+ group showed a considerably better ORR than the T+P-group (44.1% versus 30.0%). This is consistent with a previous study, reporting that patients with both tumor tissue and plasma EGFR activating mutations showed superior progressionfree survival (PFS) and overall survival (OS) compared to patients with tumor tissue mutations only [10,20]. Also, it has been reported that the sensitivity of plasma-based genotyping was associated with tumor burden [8].…”
Section: Discussionsupporting
confidence: 92%
“…Additional studies evaluating the concordance of plasma/serum and tissue EGFR mutations (Table 2) have reported a wide range of concordance rates (27.5%-100%) and sensitivities (17.1%-100%), with consistently high specificities (71.4%-100%). The disparities in sensitivities are heavily technology-dependent.Two recent meta-analyses assessing the diagnostic accuracy of cfDNA EGFR mutations demonstrated a pooled sensitivity of 61% and 67.4% and specificity of 90% and 93.5%, respectively [15,16]. Genetic interrogation of cfDNA via NGS has revealed additional mutations beyond EGFR.…”
Section: Cfdnamentioning
confidence: 99%